CLASSIFICATION OF MULTI-COMPONENT FOOD PRODUCTS FOR CUSTOMS PURPOSES - BOYDUNYK, Roksolana; SAPOZHNIK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores in depth the specific features and methodological challenges of classifying multi-component food products for customs purposes. Particular attention is paid to the fact that such products often possess characteristics similar to those of other commodity groups, contain complex multi-component formulations, or represent new and technologically advanced product varieties whose properties do not always allow for clear and straightforward identification. As a result, determining their correct classification within the framework of the Commodity Nomenclature of Foreign Economic Activity becomes significantly complicated, especially given that many of these products are not explicitly named in separate commodity positions.The purpose of the study is to analyse and systematize the difficulties that arise when applying specialized expert knowledge to determine the essential characteristics of goods required for their unambiguous customs classification. The research is based on a detailed examination of court cases related to the classification of multi-component food products, including concentrates for preparing first, second, and sweet dishes, flour-based confectionery, beverage mixes, and other products whose composition and technological processing create additional ambiguity.The findings demonstrate that inaccurate classification directly affects the implementation of customs procedures, influencing the calculation of customs duties, VAT, the application of tariff and non-tariff regulation measures, as well as compliance with prohibitions and restrictions. Misclassification leads not only to financial losses but also to legal disputes, delays in customs clearance, and increased administrative burden on both customs authorities and business entities.The article proposes a set of practical measures aimed at improving the efficiency and transparency of customs control for this category of goods. These include enhancing methodological approaches to determining essential product characteristics, expanding explanatory materials for foreign trade participants, improving expert training, and introducing clearer guidelines to minimize errors in declaring commodity codes. Implementation of these measures is expected to reduce the number of misclassification cases and court disputes, while also simplifying the work of customs authorities and ensuring more predictable regulatory conditions for businesses engaged in foreign trade.
Keywords: Commodity Nomenclature of Foreign Economic Activity; classification; terminology; identification; multicomponent food products; mixtures